The black book - Pamuk, Orhan 1952- (Farrar Straus Giroux, 1994)
An Istanbul lawyer goes in search of his missing wife and her half-brother who is a revolutionary journalist. A philosophical novel on the state of Turkey, including political oppression, pollution, Moslem fundamentalism and "Dallas." By the author of The White Castle.
Keywords: Istanbul (Turkey) -- Fiction; Fiktionale Darstellung; Legal stories; Mystery fiction